Case Report: Treatment of Delusions of Theft Based on the Assessment of Photos of Patients' Homes - Ishimaru, Daiki; Kanemoto, Hideki; Hotta, Maki; Nagata, Yuma; Satake, Yuto; Taomoto, Daiki; Ikeda, Manabu (Frontiers in Psychiatry, 2022)
Background: The occurrence of behavioral and psychological symptoms of dementia is affected by individualized context. However, details regarding delusion of theft have been poorly documented. This report describes a useful assessment to understand the environmental context of delusion through two cases of Alzheimer’s disease (AD). Familial interview was conducted to assess the phenomenological features. Photos of patients’ homes were used to increase the assessment accuracy and check the individualized environmental contexts; this is known as Photo Assessment of Living Environment (PA-LE). Case description: Case 1 was of an 88-year-old woman whose Mini-Mental State Examination (MMSE) score was 23/30. She believed that one neighbor stole her wallet and stored it on a shelf in the living room. She sometimes placed it in other places, such as under the bed as safekeeping. The delusion often occurred when getting ready to go shopping. PA-LE confirmed that the room and shelf were not cluttered, although the incorrect storage place seemed to be hard-to-find. Case 2 was of a 78-year-old woman. The MMSE score was 20/30. She believed that some neighbors stole her garden items. The delusion was limited to her garden, yet the items were varied. Auditory hallucinations exacerbated her belief that the neighbors intruded the garden. PA-LE confirmed that the garden was cluttered with several duplicated items. Moreover, the patient inaccurately remembered the condition of the garden. Non-pharmacological approaches were tailored to the patients’ environmental and psychological states, referring to the interview and PA-LE. This included environmental adjustment or increasing self-esteem. Antipsychotics were also prescribed. Environmental and psychological triggers of delusion were improved by the interventions, and the patients had uneventful courses without active delusions. Conclusion: Evaluating patients’ homes using photos could detect the environmental context of delusion of theft among patients with AD and assist in the management.